A Synergistic Approach: Enhanced Apoptotic and Proliferative Inhibition of Cisplatin by Nanocurcumin in HeLa Cells - Subandi, Subandi; Gizta, Aura Bella; Balindra, Fredlina Rossa; Handono, Kusworini; Khotimah, Husnul (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Cisplatin is a widely used chemotherapeutic agent for cervical cancer, but its effectiveness is often limited by cellular resistance and severe side effects. Curcumin has demonstrated potential to enhance cisplatin's anticancer effects by inducing apoptosis and inhibiting cell proliferation; however, its clinical use is constrained by poor solubility and low bioavailability. To overcome these limitations, liposomal nanocurcumin was developed. This study aimed to evaluate the synergistic effects of cisplatin and nanocurcumin on Bax and BrdU expression as markers of apoptosis and proliferation in HeLa cervical cancer cells. A true experimental post-test only design was employed with five groups: HeLa cell control (no treatment), positive control (cisplatin 5 µg/mL), and three treatment groups receiving cisplatin 2.5 µg/mL combined with nanocurcumin at 25, 50, and 100 µg/mL. Cells were incubated for 48 hours and analyzedusing flow cytometry. The combination treatment significantly increased Bax expression and reduced BrdU expression compared to cisplatin alone, with the strongest effect observed at 100 µg/mL nanocurcumin. These findings suggest that nanocurcumin may serve as a promising adjuvant to enhance the therapeutic efficacy of cisplatin by promoting apoptosis and suppressing proliferation in cervical cancer cells.